Place vs. Response Learning: History, Controversy, and Neurobiology - Goodman, Jarid (Frontiers in Behavioral Neuroscience, 2021)
The present paper provides a historical review of the place and response learning plus-maze tasks with a focus on the behavioral and neurobiological findings. The paper begins by reviewing the conflict between Edward C. Tolman’s cognitive view and Clark L. Hull’s stimulus-response (S-R) view of learning and how the place and response learning plus-maze tasks were designed to resolve this debate. Cognitive learning theorists predicted that place learning would be acquired faster than response learning, indicating the dominance of cognitive learning, whereas S-R learning theorists predicted that response learning would be acquired faster, indicating the dominance of S-R learning. Here, evidence is reviewed demonstrating that either place or response learning may be dominant in a given learning situation and that the relative dominance of place and response learning depends on various parametric factors (i.e. amount of training, visual aspects of the learning environment, emotional arousal, etc.). Next, the neurobiology underlying place and response learning is reviewed, indicating that place learning is principally mediated by the hippocampus, whereas response learning is mediated by the dorsolateral striatum. Other brain regions implicated in place and response learning are also discussed in this section, including the dorsomedial striatum, amygdala, and medial prefrontal cortex. An exhaustive review of the neurotransmitter systems underlying place and response learning is subsequently provided, indicating important roles for glutamate, dopamine, acetylcholine, cannabinoids, and estrogen. Closing remarks are made emphasizing the historical importance of the place and response learning tasks in resolving problems in learning theory, as well as for examining the behavioral and neurobiological mechanisms of multiple memory systems. How the place and response learning tasks may be employed in the future for examining extinction, neural circuits of memory, and human psychopathology is also briefly considered.